2007
DOI: 10.1007/s10549-007-9593-9
|View full text |Cite
|
Sign up to set email alerts
|

Phase III randomized multicenter study on the effects of adjuvant CMF in patients with node-negative, rapidly proliferating breast cancer: twelve-year results and retrospective subgroup analysis

Abstract: The randomized multicenter study on rapidly proliferating breast cancer, assessed according to thymidine labelling index (TLI), was activated at the end of the 1980s. The present work investigated whether and to what degree the short-term advantages observed from adjuvant CMF (cyclophosphamide, methotrexate, 5-fluorouracil) were maintained at a longer follow-up. Two hundred and eighty-one patients with node-negative and high TLI tumors were randomized to receive six cycles of CMF or no further treatment. At a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…In the Italian Breast Cancer Intergroup Studies (IBIS) 3 trial by Amadori and colleagues, 10 two different sequences of epirubicin and CMF (cyclophosphamide, methotrexate and fluorouracil) were compared with CMF alone in patients with rapidly proliferating BC as defined by thymidine labeling index (TLI) >3% or histological grade 3 or S-phase >10% or Ki67 >20%. 11,12 In the present study, we aimed to explore the prognostic role of PgR status in the subgroup of patients with rapidly proliferating, hormone-receptorpositive BC receiving adjuvant epirubicincontaining chemotherapy followed by tamoxifen within the IBIS 3 trial.…”
Section: Lack Of Progesterone Receptor (Pgr) Expression Is Significanmentioning
confidence: 99%
“…In the Italian Breast Cancer Intergroup Studies (IBIS) 3 trial by Amadori and colleagues, 10 two different sequences of epirubicin and CMF (cyclophosphamide, methotrexate and fluorouracil) were compared with CMF alone in patients with rapidly proliferating BC as defined by thymidine labeling index (TLI) >3% or histological grade 3 or S-phase >10% or Ki67 >20%. 11,12 In the present study, we aimed to explore the prognostic role of PgR status in the subgroup of patients with rapidly proliferating, hormone-receptorpositive BC receiving adjuvant epirubicincontaining chemotherapy followed by tamoxifen within the IBIS 3 trial.…”
Section: Lack Of Progesterone Receptor (Pgr) Expression Is Significanmentioning
confidence: 99%
“…High proliferation is a key feature in breast carcinogenesis and markers of proliferation have been shown to be associated to prognosis and to effect of adjuvant and palliative chemotherapy, to neoadjuvant endocrine therapy, and to prognosis after adjuvant endocrine treatment (Harris et al 2007; Colozza et al 2005; Beresford et al 2006; De Azambuja et al 2007; Goldhirsch et al 2009; Urruticoechea et al 2005; Hietanen et al 1995; Amadori et al 2008; Jones et al 2009; Ellis et al 2008; Viale et al 2008). Ki67 is the marker of proliferation most widely used (Goldhirsch et al 2011; De Azambuja et al 2007; Urruticoechea et al 2005; Dowsett et al 2011; Luporsi et al 2012), but the role of other markers, such as cyclin A (Bukholm et al 2001; Michalides et al 2002; Kuhling et al 2003; Baldini et al 2006; Ahlin et al 2009; Strand et al 2012) and phosphohistone H3 (Skaland et al 2007), remains under debate.…”
Section: Introductionmentioning
confidence: 99%
“…We recently demonstrated that PgR is an independent prognostic marker in rapidly proliferating hormone receptor positive early BC [ 3 ]. We would like to underline that, as already stated in our previous papers, we believe that proliferation is important to define the decision-making of adjuvant therapies in early BC [ 2 ].…”
mentioning
confidence: 91%
“…About 30 years ago, our group started a study in attempt to establish the use of chemotherapy or nothing in node negative BC with high tumor labelling index [2]. In 2008, our research group published the results from this phase 3 randomized multicenter study on the effects of adjuvant Cyclophosphamide, Methotrexate, Fluorouracil (CMF) in patients with node-negative, rapidly proliferating BC [2]. The results from twelve-year subgroup analysis showed that CMF produced a 25 and 20% relative reduction in relapse and death cumulative incidence, respectively.…”
mentioning
confidence: 99%